Adaptive compensation for actuator failures with event-triggered input - Xing, Lantao; Wen, Changyun; Liu, Zhitao; Su, Hongye; Cai, Jianping (Automatica (Oxford), 2017)
In this paper, we study the problem of event-triggered control for a class of uncertain nonlinear systems subject to actuator failures. The actuator failures are allowed to be unknown and the total number of failures could be infinite. To reduce the communication burden from the controller to the actuator, a novel event-triggered control law is designed. It is proved through Lyapunov analyses that the proposed control protocol ensures that all the signals of the closed-loop system are globally bounded and the system output tracking error can exponentially converge to a residual which can be made arbitrarily small.